Ultrasonographic Biometry of the Ovaries of Pregnant Kundhi Buffaloes - Kachiwal, Allah Bux; Sheikh, Bashir Ahmed; Sheikh, Saghir Ahmed; Qureshi, Tofique Ahmed; Memon, Maqbool Ahmed (Journal of Buffalo Science, 2012)
Sixteen gravid uteri of 1st, 2nd, 3rd and 4th month of pregnant Kundhi buffaloes were collected from Hyderabadslaughterhouse for this study. The ovaries were separated from gravid uteri of Kundhi buffaloes and ultrasonographicbiometry was performed by ultrasound machine (HS-2000, Honda electronics Co. Ltd., Japan). The ovaries wereexamined for presence of follicles and/or corpus luteum. The length, width and height of ovaries and corpus luteum (CL)were recorded and measured. The average weight of ovaries with corpus luteum during 1st, 2nd, 3rd and 4th month's ofpregnancy was 4.6 + 0.345, 5.90 + 1.134, 6.10 + 1.179, and 6.50 + 1.139 gms, respectively. The average weight of CLduring 1st, 2nd, 3rd and 4th month of pregnancy was 2.0 +0.162, 2.4 + 0.35, 2.6 + 0.27, and 3.0 + 0.49 gm, respectively.The average weight of ovaries of non-gravid uterus of same buffaloes was 2.7 + 0.35, 3.6 + 1.10, 3.9 + 1.15, and 4.2 +1.09 gm during 1st, 2nd, 3rd and 4th month of pregnancy respectively. The average size of the left and right ovary was 29.0+ 1.2 mm and 20.01 + 2.15 mm respectively and the average size of CL was 17.13 + 3.15 mm. There was significantincrease in the weight, length, width and height of ovaries and corpus leutum as pregnancy advances than non-pregnantbuffaloes. A greater number of ovarian structure (follicles) was found at the time of oestrus than anoestrus period.